SOSIALISASI DAN WORKSHOP MODEL DAN TEKNIK PEMASANGAN BATA MERAH ‘EKSPOS’ PADA KELOMPOK TUKANG ‘LAMALOGA’ - Bahantwelu, Marianus; Fanggidae, Linda W.; Kapilawi, Yohanes W.D. (Servirisma, 2025)
Red brick is the most commonly used building material in East Flores Regency, not only due to it’s availability but also because it provides aesthetic value, a natural impression, and good durability for buildings. However, many builders still lack understanding of proper and innovative installation techniques, thus the use of red bricks is limited to conventional wall partitions (which is not exposed). Through this socialization and workshop, participants were given an understanding of various models of exposed red brick installation patterns, as well as the techniques and step by step installation methods. This activity emphasizes aspects of design innovation so that builders are able to produce unique and high-value works. The implementation method includes material delivery, direct demonstration, and installation practice by participants. The results of the activity showed an increase in participant’s understanding and skills in applying aesthetic and unique red brick installation techniques. Thus, this activity is expected to improve technical skills, enhance understanding of design innovation, thereby enabling their work to achieve higher quality, refined aesthetics, and greater economic value.